2023
DOI: 10.31018/jans.v15i1.4269
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of milk source on physicochemical, texture, rheological and sensory properties of yogurts

Abstract: Yogurt is one of the world's most widely consumed dairy products and can be produced from different types of milk. The present research aimed to compare the effects of utilizing whole raw milk from  cattle viz. cows, buffaloes, sheep, and goats in four different milk-type yogurts, T1- cow’s milk (CM), T2- buffalo’s milk (BM), T3- sheep’s milk (SM), and T4- goat’s milk (GM) on their physicochemical, texture, rheological, and sensory qualities. The physiochemical testing included estimating pH, the percentages o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…This might be associated with the higher levels of protein content, which result in denser sample structures. Our findings support previous studies that have been reported by Lucatto et al [64] and Al-Bedrani et al [65]. The ratio of the positive force area during the second penetration to that during the first penetration is the definition of cohesiveness.…”
Section: Yogurts Quality 421 Texture Analysissupporting
confidence: 93%
“…This might be associated with the higher levels of protein content, which result in denser sample structures. Our findings support previous studies that have been reported by Lucatto et al [64] and Al-Bedrani et al [65]. The ratio of the positive force area during the second penetration to that during the first penetration is the definition of cohesiveness.…”
Section: Yogurts Quality 421 Texture Analysissupporting
confidence: 93%
“…The samples formulated with 40-100% of NRPO resulted in an increase in consistency values (779.34-1269.23 g•s) compared with those of the samples substituted by 40-100% HRPO (256.60-431.12 g•s). Cohesiveness represents the extent to which a material can be deformed before it ruptures [69]. The cohesiveness of the MKF sample was 16.80 g, which was significantly higher than those of the HRPO-MKF samples (9.58-10.17 g).…”
Section: Texture Profile Analysismentioning
confidence: 86%
“…Some of them are added to the manufacture of ice creams, such as dried fruits or natural sweeteners (Hasan et al, 2020;. Some of it is added in the manufacture of yogurt, such as adding dried mushroom powder, stabilizers, or different types of milk (ALKaisy et al, 2023;Al-Bedrani et al, 2023). Some of it is added in the cheese industry, such as using vegetable oils, adding cardamom, adding the enzyme trypsin in the manufacture of cheese from buffalo milk, or using a mixture of sheep and camel milk (Saadi et al, 2019;Saadi, 2018;Salih et al, 2021;Ali and Saady, 2019).…”
Section: Introductionmentioning
confidence: 99%